Ixodes scapularis nymph saliva protein blocks host inflammation and complement-mediated killing of Lyme disease agent, Borrelia burgdorferi - Bencosme-Cuevas, Emily; Kim, Tae Kwon; Nguyen, Thu-Thuy; Berry, Jacquie; Li, Jianrong; Adams, Leslie Garry; Smith, Lindsey A.; Batool, Syeda Areeha; Swale, Daniel R.; Kaufmann, Stefan H. E.; Jones-Hall, Yava; Mulenga, Albert (Frontiers in Cellular and Infection Microbiology, 2023)
Tick serine protease inhibitors (serpins) play crucial roles in tick feeding and pathogen transmission. We demonstrate that Ixodes scapularis (Ixs) nymph tick saliva serpin (S) 41 (IxsS41), secreted by Borrelia burgdorferi (Bb)-infected ticks at high abundance, is involved in regulating tick evasion of host innate immunity and promoting host colonization by Bb. Recombinant (r) proteins were expressed in Pichia pastoris, and substrate hydrolysis assays were used to determine. Ex vivo (complement and hemostasis function related) and in vivo (paw edema and effect on Bb colonization of C3H/HeN mice organs) assays were conducted to validate function. We demonstrate that rIxsS41 inhibits chymase and cathepsin G, pro-inflammatory proteases that are released by mast cells and neutrophils, the first immune cells at the tick feeding site. Importantly, stoichiometry of inhibition analysis revealed that 2.2 and 2.8 molecules of rIxsS41 are needed to 100% inhibit 1 molecule of chymase and cathepsin G, respectively, suggesting that findings here are likely events at the tick feeding site. Furthermore, chymase-mediated paw edema, induced by the mast cell degranulator, compound 48/80 (C48/80), was blocked by rIxsS41. Likewise, rIxsS41 reduced membrane attack complex (MAC) deposition via the alternative and lectin complement activation pathways and dose-dependently protected Bb from complement killing. Additionally, co-inoculating C3H/HeN mice with Bb together with rIxsS41 or with a mixture (rIxsS41 and C48/80). Findings in this study suggest that IxsS41 markedly contributes to tick feeding and host colonization by Bb. Therefore, we conclude that IxsS41 is a potential candidate for an anti-tick vaccine to prevent transmission of the Lyme disease agent.